Scaling up innovations through adaptive research: An institutional analysis and lessons from farm science centers in India - Ananth, P. N.; Sahoo, P. R.; Babu, Suresh Chandra; Barik, N. K.; Sundaray, J. K. (International Food Policy Research Institute, 2018)
This study uses a two-plot trial comparing 6 new technologies with traditional farmer practices in 34 fish farmers’ ponds in the Khordha district of Odisha state, India. The results indicate that the 6 technologies are location specific and feasible; however, some of the required inputs are out of reach for a small-scale fish farmer. The study also reveals that constant institutional support is required to keep farmers using the new practices until an incubation period has been completed. It suggests ways in which the mainstream extension system can address farmers’ constraints in order to promote more widespread adoption of new technologies. The study illustrates the challenges of conducting adaptive trials in farmers’ fields and of reaching more farmers with the proven technologies. Finally, it suggests ways to improve the technology generation system and the institutions that organize adaptive trials, as well as areas for improvement in linking results such as these to mainstream extension. Very few studies have analyzed the results of adaptive trials and their utility for both the extension system and end users.